EFEKTIFITAS PEMBERIAN PUPUK HAYATI MIKORIZA TERHADAP SERAPAN P, PERTUMBUHAN SERTA PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) DI LAHAN GAMBUT - Santosa, Catur Ahmat; Anom, Edison '; ', Murniati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aims to determine the mycorrhizal biological fertilizer dose that is effective in the absorption of P for growth and production of sweet corn on peatlands. Research has been conducted in Rimbo Panjang Village, Kampar District, Riau Province. The research lasted for four months starting in December 2015 to March 2016. The research was conducted experiments using a randomized block design (RBD) non factorial, which consists of 6 treatments and 4 replications. The observations were statistically analyzed using analysis of variance followed by Duncan's multiple range test at 5% level. Based on the survey results revealed that administration of a biological fertilizer mycorrhiza real impact on P uptake of plants, root volume, dry weight of plants, production per plot, cob diameter and number of lines of grains per ear, but the effect was not significant on plant height, ratio canopy roots, time appears male flowers, female flowers appear time, harvesting, heavy cob with husk, heavy cob without husk and cob length. Provision of biological fertilizer mycorrhizal 6 g/plant an effective dose to support the growth and the production of sweet corn on peatlands. Keywords : Biofertilizer Mycorrhizae, Sweet Corn, Peatland